Medical and psychological problems in diagnosing and treating a patient with chronic complex regional pain syndrome - Ortenburger, Dorota E.; Szerla, Małgorzata K. (Medical Studies/Studia Medyczne, 2015)
The aim of this study is to present the medical and psychological problems which occurred while diagnosing and treating a 42-year-old woman with complex regional pain syndrome (CRPS). It presents a description of somatic and emotional symptoms, social problems, and problems in diagnosis and treatment (left lower limb). Based on the described symptoms, it must be stated that there are specific premises to claim that the studied case fulfils the criteria of complex regional pain syndrome. Data concerning the patient’s psycho-emotional state were taken from a semi-structured interview, the degree of intensity of automatic negative thoughts, and psychological manifestations of hyperactivity by deep limbic system, developed by D. Amen. The patient had symptoms from a few categories, including sensation, reduced mobility, and trophic symptoms (skin lesions). Due to the complex nature of the formation of CRPS pain and associated disorders that are difficult to treat, multidisciplinary therapy was recommended.